Activation of Endogenous H 2 S Biosynthesis or Supplementation with Exogenous H 2 S Enhances Adipose Tissue Adipogenesis and Preserves Adipocyte Physiology in Humans - Comas, Ferran; Latorre, Jèssica; Ortega, Francisco; Arnoriaga Rodríguez, María; Kern, Matthias; Lluch, Aina; Ricart, Wifredo; Blüher, Matthias; Gotor, Cecilia; Romero, Luis C; Fernández-Real, José Manuel; Moreno-Navarrete, José María (Antioxidants & redox signaling, 2021)
To investigate the impact of exogenous hydrogen sulfide (H S) and its endogenous biosynthesis on human adipocytes and adipose tissue in the context of obesity and insulin resistance. Experiments in human adipose tissue explants and in isolated preadipocytes demonstrated that exogenous H S or the activation of endogenous H S biosynthesis resulted in increased adipogenesis, insulin action, sirtuin deacetylase, and PPARγ transcriptional activity, whereas chemical inhibition and gene knockdown of each enzyme generating H S ( , , ) led to altered adipocyte differentiation, cellular senescence, and increased inflammation. In agreement with these experimental data, visceral and subcutaneous adipose tissue expression of H S-synthesising enzymes was significantly reduced in morbidly obese subjects in association with attenuated adipogenesis and increased markers of adipose tissue inflammation and senescence. Interestingly, weight-loss interventions (including bariatric surgery or diet/exercise) improved the expression of H S biosynthesis-related genes. In human preadipocytes, the expression of , , and genes and H S production were dramatically increased during adipocyte differentiation. More importantly, the adipocyte proteome exhibiting persulfidation was characterized, disclosing that different proteins involved in fatty acid and lipid metabolism, the citrate cycle, insulin signaling, several adipokines, and PPAR, experienced the most dramatic persulfidation (85-98%). No previous studies investigated the impact of H S on human adipose tissue. This study suggests that the potentiation of adipose tissue H S biosynthesis is a possible therapeutic approach to improve adipose tissue dysfunction in patients with obesity and insulin resistance. Altogether, these data supported the relevance of H S biosynthesis in the modulation of human adipocyte physiology. . 35, 319-340.